Liver‐infiltrating CD8+ lymphocytes as prognostic factor for tumour recurrence in hepatitis C virus‐related hepatocellular carcinoma. (29th September 2015) - Ramzan, Muhammad; Sturm, Nathalie; Decaens, Thomas; Bioulac‐Sage, Paulette; Bancel, Brigitte; Merle, Philippe; Tran Van Nhieu, Jeanne; Slama, Rémy; Letoublon, Christian; Zarski, Jean‐Pierre; Jouvin‐Marche, Evelyne; Marche, Patrice N.; et al.
Abstract: Background: Chronic liver inflammation and immune/inflammatory response promote hepatocellular carcinoma. The aim of this study was to characterize the immune status of HCV‐related cirrhosis in patients with hepatocellular carcinoma (HCV‐HCC) as compared to HCV patients without hepatocellular carcinoma. Method: Immune markers (CD3, CD4, CD8, CD20, CD56, TCRγδ, FoxP3) and gene expression profiles (CD8α, CD8β, FoxP3, IL‐6, IFN‐γ, perforin, RANTES) were analysed in a test cohort by immunohistochemistry and quantitative RT‐PCR analysis on serial non‐tumorous and tumorous tissues. Results: Immune micro‐environment was more inflammatory in HCV‐HCC than HCV cirrhotic livers. The number of CD3 +, CD4 +, CD8 + and CD20 + liver‐infiltrating lymphocytes was significantly higher, whereas the number of CD56 + cells was significantly lower in HCV‐HCC compared to HCV cirrhotic parenchyma. These differences were restricted to fibrous septa for CD4 + and CD20 + cells and to nodular parenchyma for CD8 + cells. Gene expressions of CD8α, FoxP3 and RANTES were also significantly higher in HCV‐HCC than in HCV cirrhosis. Interestingly, in a large cohort of 63 HCV‐HCC patients. The number of CD8 + cells ≥100/field was associated with significant higher tumour recurrence ( P = 0.003) and lower overall survival ( P = 0.05) at 5 years. Conclusion: High densities of liver‐infiltrating lymphocytes in HCV‐HCC cirrhotic parenchyma prevail inflammatory conditions and could contribute to tumorigenesis and tumour recurrence. These results could contribute towards better clinical evaluation of patients susceptible for HCC recurrence after curative surgery.